KEANEKARAGAMAN LUMUT KERAK (LICHEN) SEBAGAI BIOINDIKATOR PENCEMARAN UDARA - Karisma Cahyani; Elsa Fitriani; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Air pollution is becoming an increasingly common environmental problem, driven by increasing human activity, such as transportation, industrial activity, and the use of fossil fuels. This condition can degrade air quality and potentially negatively impact the environment and the health of living things. Therefore, air quality monitoring is necessary to determine the level of pollution in an area. One approach that can be used is biomonitoring using bioindicator organisms. Lichens, or lichens, are organisms resulting from a symbiosis between fungi and algae that are known to be highly sensitive to changes in environmental conditions, particularly air quality. This study aims to examine the use of lichens as biomonitoring in detecting air pollution levels through a literature review method. The results of the study indicate that the presence, diversity, and morphological types of lichens are significantly influenced by air quality conditions in a region. Areas with good air quality generally have a higher lichen diversity than areas with high levels of pollution. Thus, lichens can be used as quite effective and relatively easy-to-implement biological indicators in environmental air quality monitoring.